Function of Host Protein Staufen1 in Rabies Virus Replication - Gaowen Liu; Congjie Chen; Ruixian Xu; Ming Yang; Qinqin Han; Binghui Wang; Yuzhu Song; Xueshan Xia; Jinyang Zhang (Viruses, 2021)
Rabies virus is a highly neurophilic negative-strand RNA virus with high lethality and remains a huge public health problem in developing countries to date. The double-stranded RNA-binding protein Staufen1 (STAU1) has multiple functions in RNA virus replication, transcription, and translation. However, its function in RABV infection and its mechanism of action are not clear. In this study, we investigated the role of host factor STAU1 in RABV infection of SH-SY-5Y cells. Immunofluorescence, TCID50 titers, confocal microscopy, quantitative real-time PCR and Western blotting were carried out to determine the molecular function and subcellular distribution of STAU1 in these cell lines. Expression of STAU1 in SH-SY-5Y cells was down-regulated by RNA interference or up-regulated by transfection of eukaryotic expression vectors. The results showed that N proficiently colocalized with STAU1 in SH-SY-5Y at 36 h post-infection, and the expression level of STAU1 was also proportional to the time of infection. Down-regulation of STAU1 expression increased the number of Negri body-like structures, enhanced viral replication, and a caused 10-fold increase in viral titers. Meanwhile, N protein and G protein mRNA levels also accumulated gradually with increasing infection time, which implied that STAU1 inhibited rabies virus infection of SH-SY-5Y cells in vitro. In conclusion, our results provide important clues for the detailed replication mechanism of rabies virus and the discovery of therapeutic targets.